Psaironeura jeronimoi (Odonata: Zygoptera: Coenagrionidae) sp. nov. from the Brazilian Amazon rainforest, with a key for species of tenuissima group, and discussion on the significance of the genital ligula to the taxonomy of the group - Mendoza-Penagos, Cristian Camilo; Juen, Leandro; Muzón, Javier; Vilela, Diogo Silva (Zootaxa, 2022)
Psaironeura jeronimoi sp. nov. is described based on seven males (Holotype: ♂ (LABECO, N° 10002717), BRAZIL, Amazonas, Alto Maués Ecological Station, (-5.9852, -59.3182, 114 m asl, 12.v.2019) collected in the state of Amazonas (near Alto Maués Ecological Station) and Pará (municipality of Belterra). This new species fits into the tenuissima group but presents differences in color pattern and shape of the apex cerci. Main morphological characters are figured and compared with those of P. tenuissima (Selys, 1886) and P. bifurcata (Sjöstedt, 1918). Key to males and comments on genital ligula of the species of the group are provided. Finally, comments on the conservation status of the species are presented.